La calidad temporal de registros en balonmano - Pic Aguilar, M. (Revista Ciencia del Deporte, 2019)
This work is an exploratory study to increase data quality control, by using temporal correlation coefficients. The consolidation of the observational methodology (Anguera, 2017) has been preceded by improvements of a different nature. It was based on an observational registration tool applied to handball and made up of criteria and categories. The study design corresponded to quadrant III, as a) nomothetic, isolated, and multidimensional. Two observers recorded handball matches (N = 4) with the help of Lince software. Statistical packages, SPSS v. 24 and JASP v. 0820, were used to associate the times of each inter-observer register and calculate the correlation coefficients among other analysis. The practical application of the work would have in the analysis of motor behavior an application but that is not the only one. Addressing the synchronization of observers when registering is a procedure open to improvement both in reliability and accuracy.